Outlook on the Carbon-Based Materials for Heavy Metal Removal - Haziqatulhanis, Ibrahim; Norazlianie, Sazali; Wan Norharyati, Wan Salleh; Nor Hasrul Akhmal, Ngadiman; Nor Akmal, Fadil; Zawati, Harun (Biointerface Research, 2022)
Carbon-based materials, including graphene (GR), carbon nanotubes (CNTs), activated carbon, and biochar, are the most common materials often applied to separate heavy metals from the water stream. A key feature of carbon adsorbent is the functional group of its adjustable surfaces. Both GR and CNTs exhibit the most favorable materials and may be the right choice in the future because of their excellent nature and unique structure. In order to commercialize the use of carbon absorbent in the removal of heavy metals, the mechanism of adsorption of carbon on heavy metals must be fully understood. In view of the good properties of carbon-based materials, a detailed study of their characteristics and synthesis, and modifications should be highlighted. Therefore, this article will discuss the properties, modifications, and use of carbon-based materials as adsorbents for various hazardous metal ions.